Foreign direct investment in Latin America from the perspective of illicit financial flows: “cocacolonisation” of saving? - Katiuska King Mantilla (CEPAL Review, 2022)
This article analyses the implications of illicit financial flows for foreign direct investment (FDI). During the 2003–2017 period, in the financing of gross fixed capital formation in Latin America, external savings show high variability in relation to domestic saving. This study calculates the net effects of FDI on the balance of payments by country, concluding that its contribution is not always positive. In fact, it is negative in countries with investments mainly in the primary or extractive sector. The volume of inward FDI is lower than recorded for all countries when considering pass-through or phantom investment, with signs of round-tripping in secrecy jurisdictions. This is of concern in countries that have traditionally kept their capital abroad. The concept of “cocacolonisation” of savings is therefore proposed.